2013
DOI: 10.1002/hed.23255
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to preventive exercises and self‐reported swallowing outcomes in post‐radiation head and neck cancer patients

Abstract: Background To reduce the risk of long-term swallowing complications after radiation, swallowing exercises may be helpful. Both the rate of adherence to swallowing exercises and its impact on future swallowing function is unknown. Methods 109 oropharyngeal cancer patients beginning radiation were tracked for two years to determine adherence to swallowing exercises. Participants completed the M.D. Anderson Dysphagia Inventory (MDADI) 1–2 years after treatment to assess self-reported swallowing function. Adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
112
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 19 publications
4
112
1
1
Order By: Relevance
“…Study patients also reported a decline in cancer-specific and dysphagiarelated qol, although satisfaction with dysphagia care improved over time. Satisfaction for qol and overall care have the potential to influence how adherent patients will be, especially with behavioural dysphagia therapy 28 . Those outcomes are therefore important confounding variables and have to be included in future therapeutic clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Study patients also reported a decline in cancer-specific and dysphagiarelated qol, although satisfaction with dysphagia care improved over time. Satisfaction for qol and overall care have the potential to influence how adherent patients will be, especially with behavioural dysphagia therapy 28 . Those outcomes are therefore important confounding variables and have to be included in future therapeutic clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of severe dysphagia as a late complication of radiotherapy in patients surviving longer than five years was performed by Hutcheson et al The total dose of radiotherapy impacted the occurrence of late dysphagia; it was observed more frequently in patients with a total dose of 70 Gy or higher [26]. Many authors have observed positive effects from proactive swallowing therapy, which were observed not just following the treatment but also 3-6 months after the completion of chemoradiotherapy and 9-12 months after treatment [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment with or without chemotherapy and radiation therapy aims to remove the tumor and increase the survival rate of subjects, for this, the mode tends to be more aggressive, and brings the short, medium and long-term consequences, impacting so significant swallowing function and global QoL of patients 9,13,17 . Chronic obstructive pulmonary disease (COPD) is a respiratory disease considered preventable and treatable, which has a significant morbidity and mortality 18 .…”
Section: Methodsmentioning
confidence: 99%